Le statut personnel des marocains à l’égard de l’ordre juridique espagnol: observations générales et propositions de lege ferenda - Andrés RODRÍGUEZ BENOT (Paix et Sécurité Internationales, 2016)
In order to regulate the personal status of Moroccans with habitual residence in Spain, it is necessary in advance to analyze the four factors that determine the legal and political framework of the issue: migratory, social, technical and religious. Secondly it is required to study the changes of the Private International Law systems in Western and Muslim countries, which increase the distance between them. Finally, this work will attempt to answer the question posed at the beginning since human communion between neighbours compel host States to establish a transnational legal framework to regulate those family situations emerged and developed in this geopolitical area